METHOD OF ANALYSIS OF OUTGOING TRAFFIC PACKAGE SIGNATURES - Petliak , Nataliia; Khokhlachova, Yuliia (Ukrainian Information Security Research Journal, 2024)
To detect outgoing malicious traffic, a method based on fuzzy logical inference has been developed to analyze signatures of outgoing traffic. The study results indicate that continuing activities in this direction are worthwhile to unload network resources during peak loads. The method verifies the signature of the outgoing traffic packet against a set of rules. The key tasks of the method are connection permission, if the packet signature is defined as permitted during classification; blocking the connection, if it is determined that the signature of the package is prohibited; and adding new signatures to existing dictionaries. During the experiment, the method confirmed its effectiveness. Having a method based on fuzzy logic for signature analysis of outgoing traffic packets has several advantages, including the detection of previously unknown attacks, reduction of the total number of cyber-attacks, prevention of overloading of network equipment, and reduction of the probability of compromise. current network.